Moscow as International Financial Center: Ideas, Plans and Perspectives - Sherstnev, Mikhail; Abramov, Dmitry; Polezhaev, Stanislav (Moskwa jako międzynarodowe centrum finansowe: plany i perspektywy, 2011)
The paper provides an overview of the Russian official plans of development of the international financial center (based primarily in Moscow) and tries to stimulate the discussion on the critical assessment of the perspectives in order to outline the efficient ways to achieve this ambitious goal.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 834-849
Keywords: Moscow; international financial development; transition economies